Risco de insegurança alimentar relacionado com comportamento parental durante a refeição e estado nutricional de pré-escolares - Fernandes, Maria Amanda Mesquita (2024)
Food Insecurity (FI) is a complex and multifaceted phenomenon that affects several aspects of child health in early childhood, influencing parental eating behaviors and impacting children's nutritional status. The objective of this study is to evaluate the relationship between the risk of food insecurity, nutritional status of preschoolers, and parental behavior during meals. This study adopts a descriptive approach, with a cross-sectional design and quantitative analysis. The study uses a descriptive approach with a cross-sectional design and quantitative analysis, being part of a cluster-randomized clinical trial. Data collection took place between October 2022 and May 2023 in twelve daycare centers in Paraíba, Ceará, and Rio Grande do Norte. The target population included preschoolers aged 2 to 5 years. Data were collected through sociodemographic questionnaires on parental eating behavior, screening for food insecurity risk, and body mass index. They were analyzed using SPSS software, version 23.0, and submitted to the chi-square test for dichotomous data, binary logistic regression, and t-test for independent samples using the bootstrap technique. The study was conducted in accordance with the guidelines of Resolution No. 466/2012 of the National Health Council and was approved by the Research Ethics Committees of the Federal University of Ceará and the Federal University of Paraíba. The final sample consisted of 732 individuals. It was found that gender (p=0.045), maternal complications during pregnancy (p=0.014), Tdap vaccination (p=0.024), and being a beneficiary of social programs (p=0.001) were significantly related to the risk of food insecurity. Vaccination against tetanus (sig=0.016), being a beneficiary of social programs (sig=0.015) and attending routine consultations in the first year of life (sig=0.025) were also identified as predictors of the risk of food insecurity. In addition, the daily availability of fruits and vegetables (p=0.013) and the practice of insisting on eating (p=0.032) were significantly higher in families with food security. It was also observed that in municipalities located in the interior of the state there is a proportion of eutrophic children compared to the capital. Given this, this study is relevant to identify the most vulnerable populations and understand the factors contributing to the risk of food insecurity in households with children in early childhood